Zika virus syndrome, lack of environmental policies and risks of worsening by cyanobacteria proliferation in a climate change scenario - Sofia Lizarralde Oliver; Helena Ribeiro (Universidade de São Paulo, 2020)
ABSTRACT Almost half of the Brazilian population has no access to sewage collection and treatment. Untreated effluents discharged in waters of reservoirs for human supply favor the flowering of cyanobacteria - and these microorganisms produce toxins, such as saxitoxin, which is a very potent neurotoxin present in reservoirs in the Northeast region. A recent study confirmed that chronic ingestion of neurotoxin-infected water associated with Zika virus infection could lead to a microcephaly-like outcome in pregnant mice. Cyanobacteria benefit from hot weather and organic matter in water, a condition that has been intensified by climate change, according to our previous studies. Considering the new findings, we emphasize that zika arbovirus is widespread and worsened when associated with climate change, especially in middle- or low-income countries with low levels of sanitation coverage.